Craig's soil mechanics - Knappett, Jonathan; Craig, R. F. (Robert F.); Craig, R. F. (Robert F.) (Abingdon, Oxon ; New York : Spon Press, 2012)
Now in its eighth edition, this text continues to blend clarity of explanation with depth of coverage to present students with the fundamental principles of soil mechanics. From the foundations of the subject through to its application in practice, the book provides an indispensable companion to undergraduate courses.
Previous ed. under : Soil mechanics / R.F. Craig.
Includes bibliographical references and index.
Keywords: Soil mechanics